1986
DOI: 10.1007/bf01711937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linolenic and eicosapentaenoic acids on prostaglandin biosynthesis and platelet function in man

Abstract: Platelet aggregation, bleeding time, prostaglandin biosynthesis and plasma cholesterol fatty acids were investigated in 12 healthy females (25-32 years), who were given different amounts of linolenic acid (0%, 4%, 8%, 12%, 16% of total energy intake) or eicosapentaenoic acid (1.7%) with formula diets for 2 weeks each. Linolenic and eicosapentaenoic acids prolonged the bleeding time and inhibited platelet aggregation and prostaglandin biosynthesis. These effects became apparent after a linolenic acid intake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Regarding the effect of EPA on thrombocyte aggregation (see below) experiments in humans have shown that the equivalent dose of ~-linolenic is approximately tenfold higher [9]. Because of the slow conversion of cz-linolenic acid to EPA and DHA in humans, these very long chain fatty acids may produce effects which are not exhibited by ~-linolenic acid.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effect of EPA on thrombocyte aggregation (see below) experiments in humans have shown that the equivalent dose of ~-linolenic is approximately tenfold higher [9]. Because of the slow conversion of cz-linolenic acid to EPA and DHA in humans, these very long chain fatty acids may produce effects which are not exhibited by ~-linolenic acid.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…To increase bleeding time, reduce platelet aggregation, and reduce prostaglandin synthesis, approximately the tenfold dose of ~-linolenic acid is needed compared to EPA [8,9]. To increase bleeding time, reduce platelet aggregation, and reduce prostaglandin synthesis, approximately the tenfold dose of ~-linolenic acid is needed compared to EPA [8,9].…”
Section: Effects Of Polyunsaturated N-3 Fatty Acids On Eicosanoid Metmentioning
confidence: 99%